EVALUATING METEOROLOGICAL DATA FOR NUCLEAR POWER PLANT (NPP) PUSPIPTEK SERPONG - Deni Septiadi; Arief Yuniarto; Agung Hari Saputra (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Precise and consistent meteorological data is needed to support safety and security as well as in an effort to meet safety requirements and criteria from the initial stages of siting, design, construction, even activities in the previous stages to the operation stage, handling safety during and during decommissioning and waste management radioactive. Therefore, the aim of this study is to identify and analyze the distribution of data distribution to see the extent to which meteorological data for nuclear site area provide accurate and precise data so that it can be used scientifically. In the present paper, the concentrations calculated by this method are compared with data observed over Portable Weather Station (PWS) and existing Automatic Weather Stations (AWS). Good agreement was confirmed in similar data observed and existing of PWS or AWS data due to statistically calculating test using correlation, deviation and Root Mean Square Error (RMSE). The two AWS tested, both Experimental Power Reactor (RDE) and Nuclear Serpong Area (KNS), gave fairly good scores statistically. Analysis on October 13, 2020, the value of RMSE, and the correlation between AWS RDE and KNS, respectively, is 361.2; 67.6 and 0.56. Then the data analysis on October 14, 2019 which compared AWS RDE and PWS, the value of Standard Deviation, RMSE, and the correlation between AWS RDE and PWS were 137.3; 8.65 and 0.48. The availability of good data is 98.3% for RDE and 95.3% for KNS, respectively.